Targeted knockdown of ribulose-1, 5-bisphosphate carboxylase-oxygenase in rice mesophyll cells - Maheshwari, Chirag; Coe, Robert A.; Karki, Shanta; Covshoff, Sarah; Tapia, Ronald; Tyagi, Aruna; Hibberd, Julian M.; Furbank, Robert T.; Quick, William Paul; Lin, Hsiang-Chun (Elsevier, 2021)
We generated antisense constructs targeting two of the five Rubisco small subunit genes (OsRBCS2 and 4) which account for between 30–40 % of the RBCS transcript abundance in leaf blades. The constructs were driven by a maize phosphoenolpyruvate carboxylase (PEPC) promoter known to have enriched expression in mesophyll cells (MCs). In the resulting lines leaf, Rubisco protein content was reduced by between 30–50 % and CO2 assimilation rate was limited under photorespiratory and non-photorespiratory conditions. A relationship between Rubisco protein content and CO2 assimilation rate was found. This was associated with a significant reduction in dry biomass accumulation and grain yield of between 37–70%. In addition to serving as a resource for reducing Rubisco accumulation in a cell-preferential manner, these lines allow us to characterize gene function and isoform specific suppression on photosynthesis and growth. Our results suggest that the knockdown of multiple genes is required to completely reduce Rubisco accumulation in MCs.